COMUNICARE MULTICULTURALĂ LA BIBLIOTECA „OVIDIUS” - GHIMPU, șef oficiu, Biblioteca „Ovidius”, Natalia (BIBLIOPOLIS, 2020)
Libraries are the institutions, which defend the right to the knowledge, promote the cultural national, regional and universal values. „Ovidius” Branch contributes to promote the multicultural communication and activities for users. We can nominate the club „Café littéraire”, collaboration with Confucius Institute „Northwest Normal University”, Lanzhou, China, the new project I want to be European. The goal of the last project is to know the European values. The library promotes the multicultural communication on Facebook and blog, in the section Multicultural communication and the section with PowerPoint presentations. The multicultural communication at the “Ovidius” Branch is extremely important today and helps to open new ways for collaborations, communications and promotion of national and international values.